Stacey the soccer fairy - Meadows, Daisy (New York : Scholastic Inc., 2010)
While everyone in Fairyland is getting ready for the Fairy Olympics, Jack Frost's goblins steal the Sports Fairies' magic objects, and without Stacey the soccer fairy's magic ball, Rachel's favorite soccer team will never reach their goal.
Originally published under title: Francesca the football fairy, with series title The sporty fairies: London : Orchard Books, 2008.
2.
006-009.
Keywords: Walker, Rachel -- (Fictitious character) -- Juvenile fiction; Tate, Kirsty -- (Fictitious character) -- Juvenile fiction; Jack Frost -- (Legendary character); Walker, Rachel -- (Fictitious character) -- Fiction; Tate, Kirsty -- (Fictitious character) -- Fiction; Fairies -- Juvenile fiction; Olympics -- Juvenile fiction; Magic -- Juvenile fiction; Goblins -- Juvenile fiction; Soccer stories; Sports stories; Fairies -- Fiction; Olympics -- Fiction; Magic -- Fiction; Jack Frost -- Fiction; Sports -- Fiction; Juvenile works; Fantasy fiction